1991
DOI: 10.1002/jor.1100090309
|View full text |Cite
|
Sign up to set email alerts
|

Type I procollagen gene expression in normal and early healing of the medial collateral and anterior cruciate ligaments in rabbits: An in situ hybridization study

Abstract: The purpose of this study was to compare the levels of procollagen type I messenger RNA (mRNA) in normal and healing medial collateral ligament (MCL) and anterior cruciate ligament (ACL) in a rabbit model. Our method of injury involved a surgical model with identical partial lacerations in the midsubstance of the MCL and ACL. Paraffin sections of normal ligaments, and ligaments 3, 7, 14, and 28 days postlaceration were studied by in situ hybridization to compare and follow the level of type I procollagen mRNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
44
0

Year Published

1992
1992
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(49 citation statements)
references
References 19 publications
5
44
0
Order By: Relevance
“…Our results on the serial change in the expression of type I procollagen gene in early healing of MCL were essentially the same as those of Wiig et al [17]. However, they did not clearly show the localization of the procollagen gene expression in the healing ligament.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Our results on the serial change in the expression of type I procollagen gene in early healing of MCL were essentially the same as those of Wiig et al [17]. However, they did not clearly show the localization of the procollagen gene expression in the healing ligament.…”
Section: Discussionsupporting
confidence: 85%
“…[14,17] In particular, there has been no report as to that of type I11 procollagen gene to our knowledge. In the present study, the healing MCL showed an increased expression of both type I and type I11 procollagen genes.…”
Section: Discussionmentioning
confidence: 98%
“…However, their expressions are only limited to the damaged area in an ACL injury. [23][24][25] It has generally been accepted that cytokines bind to their specific receptors on the cell membrane of target cells through endocrine, paracrine, or autocrine mechanisms and thereby participate in the control the various cellular functions such as gene expression, cell proliferation and differentiation, and cell product secretion by intracellular signaling pathways after their internalization and before their degradation. 26 If one were to benefit from these properties, cytokines would need to be directly and continuously injected to advance the healing process.…”
Section: Discussionmentioning
confidence: 99%
“…Existence of collagen hyperfibrils around necrotic fibroblasts in stumps of the ruptured anterior cruciate ligament provides direct evidence for collagen degradation, since the development ofthose fibrils is due to collagen interaction with proteases (Emonard et al 1991). The alterations of fibroblasts probably cause a diminished functional activity of those cells and may explain the low Type I procollagen synthesis in ruptured anterior cruciate ligaments (Wiig et al 1991). The limited capacity o f the intraligamentous fibroblasts to support the healing process might contribute to the matrix disorganization (Neurath and Stofft 1992) and to the poor healing potential of the ruptured anterior cruciate ligament.…”
Section: )mentioning
confidence: 99%